Predictive factors associated with psychological distress of caregivers of people with dementia in Japan: a cross-sectional study. (10th November 2017) - Shikimoto, Ryo; Sado, Mitsuhiro; Ninomiya, Akira; Yoshimura, Kimio; Ikeda, Baku; Baba, Toshiaki; Mimura, Masaru
ABSTRACT: Background: Caregivers of people with dementia are likely to have psychological distress that sometimes results in mental health problems, such as depression. The objective of this study was to examine some predictive factors that are thought to be associated with psychological distress of caregivers of people with dementia in Japan. Methods: Design: A cross-sectional study. Sample: As part of a study to estimate the cost of dementia in Japan, 1, 437 people with dementia-caregiver dyads were enrolled in the current informal care time study. The measurements in the study included were the basic characteristics of the caregivers and the people with dementia, and the informal care time during a week. Analysis: Factors that predict caregivers' psychological distress, which was measured by Kessler's Psychological Distress scale (K6) score, were evaluated using univariate and multivariate regression analyses. Results: Approximately 69% of the caregivers recorded a K6 score higher than 4, while 18% scored higher than 12. According to the results of the logistic regression analysis (cut-off 4/5), the K6 score was associated with mental and comorbid diseases of people with dementia, informal care time, its lower number of caregivers, and the level of nursing care. According to the results of logistic regression analysis (cut-off 12/13), the K6 score was associated with mental symptoms and comorbid disease of people with dementia, sex of caregivers, informal care time, and its lower number of caregivers. Conclusion: Our findings indicated that the psychological distress of the caregivers is quite high and that informal care time and behavioral and psychological symptoms of dementia are associated with it. These results corroborate with previous findings.